Vaccination coverage and its associated factors among children under-5 in Somalia - Mohamed Said Hassan; Faruq Abdulla; Moyazzem Hossain (BMC Public Health)
Abstract Objectives Despite global efforts to improve vaccination, the coverage of completing basic immunization (BCG, Polio 3, DPT 3, and Measles vaccines) remains unsatisfactory in Somalia. Limited research exists on the determinants influencing immunization among under-5 Somali children, highlighting the novelty of this study. This study aims to identify the coverage and factors influencing the coverage of complete basic immunization among under-5 Somali children. Methods A dataset of 9,290 children was extracted from the Somali Demographic and Health Survey-2020 (SDHS-2020). Vaccination coverage was defined as the proportion of children receiving all four basic vaccinations. The association between coverage and covariates was assessed using chi-square tests, and multivariable logistic regression identified influential determinants. Results Findings showed that the BCG was influenced by maternal education, place of residence, number of antenatal visits, and highest wealth index. The DPT3 was influenced by birth order (AOR: 0.425; 95% Cl:0.241, 0.750), maternal primary education (AOR: 1.525; 95% Cl: 1.130, 2.059), place of residence (AOR: 2.549; 95% Cl: 1.863, 3.487), number of ANC visit and wealth index; Polio 3 was influenced by the wealth index (1.883; Cl: 95%, 1.283, 2.764) and the number of prenatal care visits (AOR: 1.356; Cl: 95%, 1.043, 1.762) and measles was influenced by mother age (AOR: 3.458; 95%Cl: 1.429, 8.370), place of residence (AOR: 1.630; 95% Cl: 1.280, 2.077), number of ANC visits (AOR: 1.510; 95%, Cl: 1.074, 2.123), child age (AOR: 3.264, 95% Cl: 2.131, 5.001), birth order (AOR: 0.311; 95% Cl: 0.199, 0.486), and wealth index (AOR: 2.079; 95%, 1.496, 2.888). Conclusion Complete basic vaccination among under-5 Somali children was influenced by maternal education, age, residence, antenatal visits, household wealth, and child characteristics, e.g., place of delivery, size of child at birth, age, and birth order. Policymakers should prioritize interventions that enhance antenatal care attendance and support mothers from socioeconomically disadvantaged households.